1970
DOI: 10.3126/hren.v9i3.5581
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs for family planning in Sunsari, eastern Nepal

Abstract: Introduction: The unmet need for family planning is a very useful tool in measuring and predicting the contraceptive needs of a population. Seventeen percent of all married women would prefer to avoid pregnancy but are not using any form of family planning. In less developed countries, about one forth of pregnancies is unintended. Objective: To determine the level of unmet need for family planning and evaluate the factors that influences the unmet needs in Married Women of Reproductive Age (MRWA). Methods: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 3 publications
6
28
2
2
Order By: Relevance
“…Although unmet need decreased with the years of life below the age of 35 years, it increased with age 35 years or more. This was in line with results done in Nepal and Zambia [15] [16].…”
Section: Discussionsupporting
confidence: 81%
“…Although unmet need decreased with the years of life below the age of 35 years, it increased with age 35 years or more. This was in line with results done in Nepal and Zambia [15] [16].…”
Section: Discussionsupporting
confidence: 81%
“…This predominance of husband's desire and influence over their wives uptake of family planning method was also found in other studies done by Family Health International and Poudel IS. 13,14 Vasectomy wasn't reported in our study which showed low male participation and was a normal social attribute in south asian region. 13 …”
Section: Discussionmentioning
confidence: 92%
“…The thought process toward reproduction is similar between the contraceptive users and those who do not follow it owing to some or many combined reasons, which hinder reaching and serving these women by the family planning program. [6] In 2006, unmet need for family planning was added to the fifth Millennium Development Goal (MDG) as an indicator for tracking development on the betterment of maternal health. Hence, the eradication of unmet need could prominently decline fertility and improve maternal and child health.…”
Section: Methodsmentioning
confidence: 99%